A functional analysis of the Finnish 2012 presidential debates - Paatelainen, Laura (2016)
English: Functional theory of political campaign discourse has been applied widely to analysis political campaign discourse, especially political debates. However, there have been claims that the theory is not a suitable tool for analysing political debates outside the United States. In this paper the functional theory of political campaign discourse is applied to the analysis of Finnish 2012 presidential debates. In addition to forming a clearer picture of Finnish political campaign discourse, the aim is to compare the results to those reached in the United States and to reach a better understanding of possible differences between the two political cultures. Finally, the paper poses a question: to what extent is functional theory of political campaign discourse a suitable tool for analysing political campaign discourse in Finland?